1989
DOI: 10.3109/07357908909017528
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Human Lung Cancer Cells Using a New [111In]Bleomycin Complex [111In]BLMC

Abstract: The ability of a [111In]bleomycin complex [( 111In]BLMC) to kill five cell lines of human lung cancer (small cell lung cancer) was investigated. Cells were exposed to either 0.9% NaCl, [111In]Cl3, BLM, [111In]BLMC, nonradioactive InCl3, or In-BLMC for 60 minutes, plated in soft agarose, and assessed for colony formation. [111In]BLMC (40-200 microCi carried by 15-25 micrograms BLM/ml) was more cytotoxic than BLM (15-25 micrograms BLM/ml) by a factor of 1.6-5.3 for five cell lines. The percent survival of N417 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Our previous data [9] also indicated that there were no significant difference in cell survival between the Table 11.…”
Section: Chromatid and Chromosome Aberrationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Our previous data [9] also indicated that there were no significant difference in cell survival between the Table 11.…”
Section: Chromatid and Chromosome Aberrationsmentioning
confidence: 86%
“…Human small cell lung cancer (SCLC) is sensitive to chemotherapy, radiotherapy, and combined chemo-radiotherapy [8]. Experiments with ' ' 'In-BLMC showed that it was more cytotoxic than BLM by a factor of I .6-5.3 times for killing five human SCLC cell lines [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumours were palpable after 12-14 days and were used after reaching a volume of approximately 8 cm 3 (longest dimension: 2.5 cm). Bleomycin (Blenoxane, Mead Johnson, Princeton, NJ) was labelled with 111 In by mixing 1 mCi (0.1 ml) of 111 InCl (Nycomed Amersham, Amersham, England) with 0.4 ml bleomycin solution (10 mg = 15 units bleomycin, per ml normal saline, acidified with cHCl to pH 1-3), letting the mixture stand for 1 h at room temperature with occasional mixing, and adding another 0.5 ml bleomycin solution and 1.0 ml acidified normal saline to the mixture [49][50][51]. Labelling efficiency was approximately 97% as determined by thin layer chromatography on silica gel (liquid phase: equal volumes of MeOH and 10% aqueous ammonium acetate; Rf approximately 0.7).…”
Section: In-bleomycin Pharmacokineticsmentioning
confidence: 99%
“…Thus, Auger electron emitting radionuclides hold great promises in systemic radiotherapy if appropriate carriers can be found. Attempts have been made to develop chemo-Auger combination therapy with Auger emitters labelled to bleomycin (86,87) and carboplatin (88,89). Many cancer cells contain hormone receptors in the cytoplasm or on the cell membrane, to which hormones or anti-hormone drugs labelled with an Auger electron emitting radionuclide may be targeted.…”
Section: Therapy With Low Energy Electronsmentioning
confidence: 99%